THE INFLUENCE OF TECHNOLOGY IN LOGISTICS: An Exploratory Study - Correia da Silveira Batista, Haydée Maria; Meirelles Drumond, Geisa; Dias, Ana Claudia; da Cunha Reis, Augusto; Picinini Méxas, Mirian (Perspectivas Contemporâneas, 2019)
Advances in technology enable companies to collect and analyze previously inaccessible data to improve existing business processes or create new ones. The purpose of this study is to document the role and impact of technology in supporting business strategy with regard to logistics, addressing Social Network Analysis (SNA), Big Data Analytics (BDA) and the Internet of Things (IoT) in order to assist in the continuous improvement of the quality of services and respective costs. This study was elaborated from a literature review researched in the Scopus and Web of Science bases from where 56 articles were extracted, period 2000/2018, besides books and statistical consultations. The state of art has revealed that with the many possibilities that technology offers today, a better dynamics of logistics management can be achieved by storing data directly in the cloud that help to signal ideal times and places of purchase, inventory control, storage and displacement of the products, allowing to predict maintenance schedules and predictive and proactive movement. Despite the various benefits, it has been found that investment in technology in the logistics area is still quite high, observing that recently some companies are beginning to realize the benefits of this high investment in technology in the supply chain area. The findings of this research serve as a valuable example of how logistics can take advantage of the deployment of SNA, BDA and IoT technologies, assisting professionals, researchers and society in general.